Atomic Spectrometry Update. Atomic Mass Spectrometry - Bacon, J.; Linge, Kathryn; Parrish, R.; Van Vaeck, L. (Royal Society of Chemistry, 2008)
The review this year is dominated by the large number of publications on AMS, ICP-MS and SIMS. The increasing number of new AMS installations bears witness to the increasing interest in the technique now that smaller and simpler systems are becoming more widely available. Although high- energy systems still have an important role to play, each of the new systems was compact and of relatively low- energy. The development of ion sources that can accept gaseous samples has lowered the sample size requirement for radiocarbon analysis such that it is now little more than the background level. Contamination therefore has become a major issue. The numerous papers on improvements to SIMS analysis demonstrate the important role the technique plays in materials science. Unlike for most of the techniques covered, fundamental studies on SIMS analysis abound with particular attention being paid to understanding the ionization processes and the representativeness of the measured ion beam. Quantum chemistry calculations have been used to determine the fundamental processes occurring in cell ICP- MS. This approach contrasted with the empirical studies that are normally undertaken. Although many applications are still being published using collision and/ or reaction cell ICP- MS, there were fewer novel or fundamental studies than in previous years. This suggests that cell ICP-MS is becoming a more routine method of analysis. The same can probably also be said of hyphenated ICP- MS methods for speciation, which continues to grow in importance but which is very much at the applied end of the spectrum. Speciation is notable in that it cuts across a number of MS techniques and conventional organic MS techniques are increasingly being investigated for structure determination of organometallic species. Each year seems to find further expansion of MC- ICP-MS into 'non-traditional' isotope analysis. This was the year for Ti isotope analysis.